1996
DOI: 10.1111/j.1443-1661.1996.tb00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Histogenesis of 6‐10 mm Early Colorectal Cancer Different from that of Larger Cancers?

Abstract: Out of a total of 466 cases of early colorectal cancer, we analyzed 139 cases with submucosal invasion (sm cancer) according to tumor size, gross appearance, depth and degree of invasion, and the presence of adenoma components. Early colorectal cancers 11 ‐20 mm in diameter were the most common lesion in this group, and the percentage with sm cancer increased with tumor size. More than 70% of relatively small sm cancers, 6‐10 mm in diameter, had moderate or massive submucosal invasion similar to that found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
1
Order By: Relevance
“…Kikuchi et al described three lesions with massive cancer involvements into the submucosal layer, but did not describe their macroscopic morphology or endoscopic findings 9 . Saitoh et al , Kodaira et al and Machida et al all found no differences in endoscopic findings of ordinary minute adenomas and minute sessile cancers, including the massive cancer involvement 1,8,10 . However, our case was distinguished from these previous cases by the bleeding spots on the surface of the minute lesion.…”
Section: Discussioncontrasting
confidence: 61%
“…Kikuchi et al described three lesions with massive cancer involvements into the submucosal layer, but did not describe their macroscopic morphology or endoscopic findings 9 . Saitoh et al , Kodaira et al and Machida et al all found no differences in endoscopic findings of ordinary minute adenomas and minute sessile cancers, including the massive cancer involvement 1,8,10 . However, our case was distinguished from these previous cases by the bleeding spots on the surface of the minute lesion.…”
Section: Discussioncontrasting
confidence: 61%